Actividades de expresión corporal para desarrollar la identidad y autonomía personal de los niños y niñas de 4 a 5 años del segundo nivel de educación inicial de la escuela Alonso de Mercadillo de la ciudad de Loja, periodo septiembre 2013-julio 2014 - Gumán Jiménez, Enith (2015)
This investigation: "Activities of corporal expression for developing personal identity and autonomy in children of four to five years in the second level first education, in the school Alonso de Mercadillo, Loja, period september-2013/july-2014, it has been prepared in accordance with Academic Regulation System of the National University of Loja. The objectives: - Identify the base theory of the activities of corporal language, identity and personal autonomy in children of four to five years of second level first education, in the school Alonso de Mercadillo, Loja. - Identify the difficulties of identity and personal autonomy in children of four to five years of second level first education, in the school Alonso de Mercadillo, Loja. - Organize a program of activities the corporal language to increase personal identity and autonomy in children in the second level first education, in the school Alonso de Mercadillo, Loja. - Implement the program of activities the corporal language to increase personal identity and autonomy in children of four to five years of second level first education - Validate the relevance of the work program of physical expression to increase personal identity and autonomy in children in the second level first education, in the school Alonso de Mercadillo, Loja. The methodology used: analytical, descriptive, hermeneutical, statistical and deductive method; various techniques are used: the questionnaire applied to the teacher of second level first education, in the school Alonso de Mercadillo, Loja. Test psycho-educational results applied in children of second level first education, and observation file that allowed identify problems in children and evaluate the program of activities of corporal expression. The investigation results indicate that the proposal was applied to solve problems in children was highly effective, applied activities reduced the difficulties in children with respect to identity and personal autonomy, activities also applied motivated teacher to replicate in the teaching-learning process and so to obtain positive learning in their students.